2015
DOI: 10.1016/j.chemphys.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutual vibrational quenching in CO + H2 collisions

Abstract: Vibrational quenching of CO and H 2 is studied quantum mechanically for collisions where both molecules are vibrationally excited. A five-dimensional (5D) coupled states (CS) approximation is used to formulate the dynamics. The approximation is tested against six-dimensional (6D) results for CO+H 2 with single vibrational excitation using both the CS approximation and the full close-coupling (CC) method.The 5D approximation is shown to provide a practical and reliable numerical approach for obtaining state-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…11,12 The CS approximation has been successfully implemented in H 2 +H 2 and CO+H 2 rovibrational scattering calculations and achieved reasonable agreement with CC results. 11,12 However, in this work we adopt the CC method.…”
Section: Introductionmentioning
confidence: 82%
“…11,12 The CS approximation has been successfully implemented in H 2 +H 2 and CO+H 2 rovibrational scattering calculations and achieved reasonable agreement with CC results. 11,12 However, in this work we adopt the CC method.…”
Section: Introductionmentioning
confidence: 82%
“…Previous work 16 showed that 5D-CS and 6D-CS results for CO+H 2 were virtually identical for collision energies above 10 cm −1 . The agreement with 6D-CC calculations was also found to be good at these energies for the limited amount of data that was available for comparison.…”
Section: Resultsmentioning
confidence: 88%
“…Collisions of molecular hydrogen with CO are important processes in astrophysical environments and has attracted considerable experimental and theoretical attention in recent years [41][42][43][44][45][46][47][48][49][50][51]. Its importance stems from the fact that CO is the second most abundant molecule in the interstellar medium after H 2 and is often used as a tracer of H 2 in dense interstellar clouds due to its dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…Its importance stems from the fact that CO is the second most abundant molecule in the interstellar medium after H 2 and is often used as a tracer of H 2 in dense interstellar clouds due to its dipole moment. Several theoretical studies have reported temperature dependent rate coefficients for rotational and rovibrational transitions in CO due to H 2 collisions of interest in astrophysical media [43,[46][47][48][49][50][51]. Highly accurate measurements of CO rotational excitation cross sections by H 2 have also been reported allowing direct comparisons with theoretical predictions [46-48, 50, 51].…”
Section: Introductionmentioning
confidence: 99%